Synthesis and antibacterial activity of some new schiff bases and 2-Azetidinones containing iodohyydroxy biphenyl moiety - Junne, Subhash B; Kadam, Archana B; Zangade, Sainath B; Shinde, Saheb L; Vibhute, Yeshwant B (International Multidisciplinary Research Journal, 2012)
2-Hydroxy-5-phenylbenzaldehyde on iodination yielded 2-Hydroxy-3-iodo-5-phenylbenzaldehyde. This aldehyde on facile condensation with substituted aromatic amines in presence of catalytic amount of acetic acid to afford new series of Schiff bases. Further these Schiff bases on cyclocondensation reaction with chloroacetyl chloride afforded a biologically active 2-azetidinones derivatives. The structure of newly synthesized compounds characterized on the basis of elemental analysis and spectral data. The compounds prepared were tested against Xanthomonas citri, Escherichia coli, Erwinia carotovora and Bacillus subtilis. Some of these compounds showed potential antibacterial activity.